The role of World Health Organization and Information Technology in improving patient safety through reducing medical errors. - Hamid Moghaddasi (Archives of Community Medicine and Public Health - Peertechz Publications, 2019)
When it comes to medical errors, everyone cites the statistics provided by the Institute of Medicine. The statistics is provided continually by the American Medical Community and refl ects their tendency in reducing medical errors and increasing the level of patient safety [1-4]. However, most countries in the world try to hide the ineffi ciency of the members of their health care team, especially physicians [5-8]. The term "medical error" is associated with medical ineffi ciency, but its defi nition indicates the possibility of an error by any member of the health care team, including the physician and nurse [9]. Therefore, it is suggested that the term "Health care error" be used to refer to care ineffi ciency by any members of the care team, regardless of their particular fi eld of specialty, whereas fi eld oriented terms like "nursing errors" or "medical errors" could be used to indicate errors happening in any specifi c subfi elds of health care. With this reasoning, the phrase "medical errors" that has been used in this text, would refer to the errors related to medical discipline.